Dividend Policy Determinants : An Experiential Study of Financial Markets - Wadhwa, Ritu (Indian Journal of Finance, 2024)
Purpose : The purpose of the study focused on discovering whether the dividends declared by the companies were affected by the sectors to which they belonged. This study also scrutinized various explanatory variables for dividend payment amongst multiple segments in India. Methodology : Due to many industries, investment avenues, and various sectors, India was considered for this research study. The analysis used balanced panel data comprising firms listed on the NSE (National Stock Exchange) for 10 years, i.e., 2013–2022. The fixed effect model (FEM) and Pooled OLS regression (POLS) were employed in the study. Findings : The research findings explained that profitability and size positively impacted Indian companies’ dividend policy. The sectorized outcome showed that size and profitability were critical determinants of dividend policy across most sectors. Practical Implications : Policymakers could use this study’s outcome to make effective dividend payout decisions. Most importantly, investors could utilize the findings to make portfolio selections based on sectorized dividend payment behavior. The research authenticated that the factors impacting dividend policy varied across various sectors. Originality : In contrast to earlier studies, this research incorporated critical variables to analyze the dividend policy of the NIFTY 500 and examined their impact on dividend decisions across various sectors within the defined index.